Historical Perspective and Biotechnological Trends to Block Arboviruses Transmission by Controlling Aedes aegypti Mosquitos Using Different Approaches - Rodrigues-Alves, Marina Luiza; Melo-Júnior, Otoni Alves de Oliveira; Silveira, Patrícia; Mariano, Reysla Maria da Silveira; Leite, Jaqueline Costa; Santos, Thaiza Aline Pereira; Soares, Ingrid Santos; Lair, Daniel Ferreira; Melo, Marília Martins; Resende, Lucilene Aparecida; da Silveira-Lemos, Denise; Dutra, Walderez Ornelas; et al. (Frontiers in Medicine, 2020)
Continuous climate changes associated with the disorderly occupation of urban areas have exposed Latin American populations to the emergence and reemergence of arboviruses transmitted by Aedes aegypti. The magnitude of the financial and political problems these epidemics may bring to the future of developing countries is still ignored. Due to the lack of effective antiviral drugs and vaccines against arboviruses, the primary measure for preventing or reducing the transmission of diseases depends entirely on the control of vectors or the interruption of human-vector contact. In Brazil the first attempt to control A. aegypti took place in 1902 by eliminating artificial sites of eproduction. Other strategies, such as the use of oviposition traps and chemical control with dichlorodiphenyltrichlorethane and pyrethroids, were successful, but only for a limited time. More recently, biotechnical approaches, such as the release of transgenics or sterile mosquitoes and the, development of transmission blocking vaccines, are being applied to try to control the A. aegypti population and/or arbovirus transmission. Endemic countries spend about twice as much to treat patients as they do on the prevention of mosquito-transmitted diseases. The result of this strategy is an explosive outbreak of arboviruses cases. This review summarizes the social impacts caused by A. aegypti-transmitted diseases, mainly from a biotechnological perspective in vector control aimed at protecting Latin American populations against arboviruses.